A Gene Encoding a Holin-Like Protein Involved in Spore Morphogenesis and Spore Germination in Bacillus subtilis - Real, Gonçalo (American Society for Microbiology, 2005)
We report here studies of expression and functional analysis of a Bacillus subtilis gene, ywcE, which codes for a product with features of a holin. Primer extension analysis of ywcE transcription revealed that a single transcript accumulated from the onset of sporulation onwards, produced from a σ(A)-type promoter bearing the TG dinucleotide motif of “extended” −10 promoters. No primer extension product was detected in vivo during growth. However, specific runoff products were produced in vitro from the ywcE promoter by purified σ(A)-containing RNA polymerase (Eσ(A)), and the in vivo and in vitro transcription start sites were identical. These results suggested that utilization of the ywcE promoter by Eσ(A) during growth was subjected to repression. Studies with a lacZ fusion revealed that the transition-state regulator AbrB repressed the transcription of ywcE during growth. This repression was reversed at the onset of sporulation in a Spo0A-dependent manner, but Spo0A did not appear to contribute otherwise to ywcE transcription. We found ywcE to be required for proper spore morphogenesis. Spores of the ywcE mutant showed a reduced outer coat which lacked the characteristic striated pattern, and the outer coat failed to attach to the underlying inner coat. The mutant spores also accumulated reduced levels of dipicolinic acid. ywcE was also found to be important for spore germination.